The other ducks - Yeomans, Ellen, 1962- (Roaring Brook Press, 2018)
This Duck and That Duck get along swimmingly. But sometimes two ducks just aren't enough. Especially when you want to waddle in a line. On a bright sunny day, This Duck and That Duck gaze into the clear water of their pond and discover, to their surprise and delight ... The Other Ducks. But what happens when the days turn cloudy and gray?"--Page [2] of cover.